rTMS over bilateral inferior parietal cortex induces decrement of spatial sustained attention - Lee, Jeyeon; Ku, Jeonghun; Han, Kiwan; Park, Jinsik; Lee, Hyeongrae; Kim, Kyung Ran; Lee, Eun; Husain, Masud; Yoon, Kang Jun; Jang, Dong Pyo; Kim, In Young; Kim, Sun I. (Frontiers in Human Neuroscience, 2013)
Sustained attention is an essential brain function that enables a subject to maintain attention level over the time of a task. In previous work, the right inferior parietal lobe (IPL) has been reported as one of the main brain regions related to sustained attention, however, the right lateralization of vigilance/sustained attention is unclear because information about the network for sustained attention is traditionally provided by neglect patients who typically have right brain damage. Here, we investigated sustained attention by applying a virtual lesion technique, transcranial magnetic stimulation (TMS), over the left and right superior parietal lobe (SPL) and IPL. We used two different types of visual sustained attention tasks: spatial (location based) and non-spatial (feature based). When the participants performed the spatial task, repetitive TMS (rTMS) over either the right or left IPL induced a significant decrement of sustained attention causing a progressive increment of errors and response time. In contrast, participants' performance was not changed by rTMS on the non-spatial task. Also, omission errors (true negative) gradually increased with time on right and left IPL rTMS conditions, while commission errors (false positive) were relatively stable. These findings suggest that the maintenance of attention, especially in tasks regarding spatial location, is not uniquely lateralized to the right IPL, but may also involve participation of the left IPL.